2018
DOI: 10.17695/issn.2317-7160.v16n1a2018p64-72
|View full text |Cite
|
Sign up to set email alerts
|

Brinquedo Terapêutico: Preparo De Crianças Em Idade Pré-Escolar Para Punção Venosa

Abstract: No período de hospitalização, a criança passa a vivenciar situações de estresse, decorrentes da mudança de rotina e do afastamento da família e dos amigos. Por essa razão, em um ambiente hospitalar, é necessário utilizar estratégias de enfrentamento que reduzam os prejuízos ao desenvolvimento, o que nos leva a averiguar a eficácia do uso do brinquedo terapêutico dramático no preparo de crianças em idade pré-escolar para procedimentos de enfermagem. Método: pesquisa do tipo intervenção, realizada com cinco pré-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…This result is in line with the objectives proposed by this instrument, which is seen as a tool capable of mitigating the suffering and trauma resulting from hospitalization, and consequently carrying out invasive procedures. 13,15,19 Favoring the child's understanding of the procedures to which they will be submitted, and the real benefits of these for their health, is one of the main objectives of the ITP practice, which aims to enable the dramatization of the procedure by the child, with the purpose of reducing the levels of anxiety, fear, tension, anguish and suffering presented by these.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in line with the objectives proposed by this instrument, which is seen as a tool capable of mitigating the suffering and trauma resulting from hospitalization, and consequently carrying out invasive procedures. 13,15,19 Favoring the child's understanding of the procedures to which they will be submitted, and the real benefits of these for their health, is one of the main objectives of the ITP practice, which aims to enable the dramatization of the procedure by the child, with the purpose of reducing the levels of anxiety, fear, tension, anguish and suffering presented by these.…”
Section: Discussionmentioning
confidence: 99%
“…15 This result was similar to that obtained in the study about the use of therapeutic plays in the preparation of children of preschool age for venipuncture, who found that one of the children understood venipuncture only as a means of obtaining a cure for the disease, and return to residence, without knowing for sure how the medication works and its benefits for the improvement of your clinical condition. 19,21 When the child has the opportunity to play and dramatize IVT, through ITP, the pain, loneliness, fear and crying are alleviated. Corroborating the results of contemporary studies on the use of ITP to prepare hospitalized children for IVT, 5,21,23,25,26 it was possible to glimpse the expression of positive responses of the child after this technique, of which we can mention: the reduction of fear; tranquility before the procedure; the relaxed posture; the cooperation of the child; the greater interaction with the health team and other children hospitalized and the reduction of tension levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tal realidade impõe a necessidade de estratégias para minimizar esse sofrimento, especialmente no que tange o preparo da criança para vivenciar esse momento de forma menos traumática, principalmente entre pré-escolares, faixa etária prevalente nessa pesquisa. Nessa vertente, a literatura aponta como possibilidade a utilização do brinquedo terapêutico (27) , inclusive nos moldes de aplicativo (app) (26) .…”
Section: Discussionunclassified
“…Among these health care, there is dental treatment, which has been the object of study, as these psycho-affective reactions influence the postponement of demand for dental professionals and, consequently, in poor oral health conditions. Oral diseases are a public health issue because they have a high prevalence, but they also cause individual and collective impacts regarding pain, discomfort, social and functional limitations that affect the individual's quality of life (Pessoas, Santos, Cruz, Marques & Lubenow, 2018). As a result of these implications, research has shown interference in oral health care due to anxiety and fear caused by dental treatment (Bottan, Lehmkuhl & Araújo, 2008;Hass, Oliveira & Azevedo, 2016;Martins, Belila, Garbin, C. A. S., & Garbin, 2017;Sanshatone, Bolsson, Pereira, Carpes & Santos, 2017;Soares, Lima, Barreto & Colares, 2015).…”
Section: Introductionmentioning
confidence: 99%